ANALYSING SPARE PARTS FORECAST ACCURACY FOR CIVIL AEROSPACE IN ROLLS-ROYCE - Welburn, Matthew (2011)
A modern Civil Aerospace organisation like Rolls-Royce is dependent on readily available spare parts for in-service aircraft in order to maximise operational capability. After sales service is of growing importance to the Rolls-Royce business. In order to provide good service to its customers Rolls-Royce need to ensure the availability of spare parts needed in repair and maintenance operations. Forecasting plays an important part in the availability of spare parts . Forecast accuracy for spare parts is highly dependent on the demand signal from the customer. A large proportion of parts are erratic or slow-moving demand and these present particular problems as far as forecasting and inventory control are concerned.